Decarboxylative Suzuki–Miyaura coupling of (hetero)aromatic carboxylic acids using iodine as the terminal oxidant. Issue 45 (17th May 2019) - Quibell, Jacob M.; Duan, Guojian; Perry, Gregory J. P.; Larrosa, Igor
Abstract : A novel methodology for the decarboxylative Suzuki–Miyaura-type coupling of carboxylic acids with arylboronic acids has been developed. Abstract : A novel methodology for the decarboxylative Suzuki–Miyaura-type coupling has been established. This process uses iodine or a bromine source as both the decarboxylation mediator and the terminal oxidant, thus avoiding the need for stoichiometric amounts of transition metal salts previously required. Our new protocol allows for the construction of valuable biaryl architectures through the coupling of (hetero)aromatic carboxylic acids with arylboronic acids. The scope of this decarboxylative Suzuki reaction has been greatly diversified, allowing for previously inaccessible non- ortho -substituted aromatic acids to undergo this transformation. The procedure also benefits from low catalyst loadings and the absence of stoichiometric transition metal additives.